Prosocial competence in students: diagnosis and psychoeducational proposal - Cañas Betancur, Dora Cristina; Gámez Murcia, Marleidy (Rastros Rostros, 2020)
The objective of this study was to make a diagnosis of prosocial competence versus the sex and age variables of 131 primary school students and, based on the findings, to design and apply a psychoeducational intervention. This research was quantitative, with a quasi-experimental design, cross-section-al and descriptive in scope. For the pretest-posttest evaluation of prosocial competence, the Spanish adaptation of the Prosocial Behavior Scale was used (Del Barrio, Moreno y López, 2001). The results indicated statistically significant differences after the intervention (based on prosocial games) between the control and experimental groups, with a higher mean for the latter in the sympathy and help factor, which leads to reaffirm the relevant role of the school as the space where changes can be promoted in individuals that will contribute to a better quality of life of a society.